Volume 8: Polar and Arctic Sciences and Technology; Petroleum Technology 2017
DOI: 10.1115/omae2017-61391
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Flow Modelling Approach for Kick Tolerance Calculations

Abstract: During drilling, there must be an evaluation of the maximum pressure that the formation can handle during a well kill scenario. This will depend on various parameters like fracture pressure, pore pressure, kick volume and several other factors. The depth of the next planned hole section will depend on if a kick of a certain size can be handled safely. This evaluation is often referred to as performing kick tolerances. When starting to drill a section, one will take a leak off test to get an indication of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When planning the length of the next open hole section, it is important to determine what type of wellbore pressure will occur in the open hole section when an unexpected gas kick needs to be controlled to avoid underground blowouts if the fracture pressure is exceeded [1]. Typically, the weakest point in the open hole section is the last casing shoe in the wellbore.…”
Section: Principle Calculation Of Kick Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…When planning the length of the next open hole section, it is important to determine what type of wellbore pressure will occur in the open hole section when an unexpected gas kick needs to be controlled to avoid underground blowouts if the fracture pressure is exceeded [1]. Typically, the weakest point in the open hole section is the last casing shoe in the wellbore.…”
Section: Principle Calculation Of Kick Tolerancementioning
confidence: 99%
“…Since kick tolerance (KT) was considered a crucial feature, its effects on well planning, drilling, and well control were measured [1]. It has been reported that a practical method for measuring KT in good planning has been applied to wells in the Canadian Beaufort Sea, which has high abnormal pressure and unconsolidated formation, as well as permafrost, gas hydrates, and plastic shale [2].…”
Section: Introductionmentioning
confidence: 99%